Foaming properties of egg white proteins improved by enzymatic hydrolysis: The changes in structure and physicochemical properties. (August 2023) - Lyu, Siwen; Chen, Meiru; Wang, Ying; Zhang, Deju; Zhao, Songning; Liu, Jingbo; Pan, Fengguang; Zhang, Ting
Abstract: Hydrolysis can affect the foaming capacity and stability of egg white protein (EWP), while the relevance of structure and foaming properties were not elucidated. Herein, the changes of structure, physico-chemical and foaming properties of EWP hydrolysates with different hydrolysis times were investigated. The foaming ability was increased from 69.67 to 108.33% after 15 min of neutral protease-mediated hydrolysis. The results also indicated hydrolysis process increased the ratio of the polypeptides with small molecular weight (<10 kDa), this condition promotes EWP's adsorption to the air-water interface. Besides, intrinsic fluorescence spectroscopy indicated that the EWP's structure occurred to unfoldment and exposed to environment with strong polarity in hydrolysis, while the free sulfhydryl contents were increased. Meanwhile, the result of Fourier transforms infrared spectrometry confirmed these structural changes. This research demonstrated that enzymatic hydrolysis might become a beneficial method to obtain dominant foaming agents in the food process and industry. Graphical abstract: Image 1 Highlights: Moderate hydrolysis can improve the foaming property of egg white protein. The 15 min hydrolysate had the most compact and uniform foam. Molecular weight reduction of egg white protein benefits to foaming properties. The interchange reactions of SH-SS conduct a contrary effect of foaming property.